Existence and multiplicity of solutions for the Kirchhoff equations with asymptotically linear nonlinearities. (December 2015) - Li, Lin; Sun, Ji-Jiang
Abstract: In this paper we study the nonlinear Kirchhoff equations on the whole space. We show the existence, non-existence, and multiplicity of solutions to this problem with asymptotically linear nonlinearities. This result can be regarded as an extension of the result in Li et al. (2012).